An empirical study on the rural development policies in Andhra Pradesh (International Journal of Food and Nutritional Sciences, 2019)
Rural development is a critical aspect of socio-economic progress influencing the well-beingand empowerment of individuals and communities. In Andhra Pradesh state, India, Ruraldevelopment policies play a vital role in addressing Rural disparities, promoting Rural equality,and empowering women. This empirical study aims to examine the effectiveness and impactof Rural development policies implemented in AP state, focusing on their contributions tosocio-economic development, women's empowerment, and overall Rural equality.